2018
DOI: 10.1111/tpj.14061
|View full text |Cite
|
Sign up to set email alerts
|

Diverse paths to hybrid incompatibility in Arabidopsis

Abstract: Summary One of the most essential questions of biology is to understand how different species have evolved. Hybrid incompatibility, a phenomenon in which hybrids show reduced fitness in comparison with their parents, can result in reproductive isolation and speciation. Therefore, studying hybrid incompatibility provides an entry point in understanding speciation. Hybrid incompatibilities are known throughout taxa, and the underlying mechanisms have mystified scientists since the theory of evolution by means of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 140 publications
(203 reference statements)
0
28
0
Order By: Relevance
“…Being able to predict hybrid performance -both whether hybrids are better or worse than their parents -is highly valuable in plant breeding. While heterosis or hybrid vigor are desirable, hybrid weakness, with hybrid necrosis being one prominent example among many [12,64], must be avoided. Most, but not all, previously identified hybrid necrosis loci in A. thaliana seem rare [20,22,65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being able to predict hybrid performance -both whether hybrids are better or worse than their parents -is highly valuable in plant breeding. While heterosis or hybrid vigor are desirable, hybrid weakness, with hybrid necrosis being one prominent example among many [12,64], must be avoided. Most, but not all, previously identified hybrid necrosis loci in A. thaliana seem rare [20,22,65].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the combination of divergent germplasm, which is an important source of novel variation in breeding, also incurs the risk of genetic incompatibilities. In plants, a particularly conspicuous set of incompatibilities is associated with autoimmunity, often with substantial negative effects on hybrid fitness [11][12][13]. Studies of hybrid autoimmunity in several species, often expressed as hybrid necrosis, have revealed that the underlying genetics tends to be simple, with often only one or two causal loci.…”
Section: Introductionmentioning
confidence: 99%
“…Since the consequences of inappropriate activation are so profound, it seems likely that NLRs and the proteins that regulate their activity co‐evolve and that divergence of these proteins may occur within subpopulations of a species with low population gene flow. Within the genus Arabidopsis , the progeny of some crosses between species, or between distant accessions within a species, grow poorly and display a necrotic leaf phenotype (Chae et al , ; Vaid and Laitinen, ). In a number of these cases of so‐called hybrid necrosis, the causal genes are NLRs, one from each parent (Bomblies and Weigel, ).…”
Section: Consequencesmentioning
confidence: 99%
“…Post-zygotic, genetic isolation is thought to occur due to epistatic interaction between loci, where alleles arise and fix in allopatry prior to secondary contact, e.g., the Bateson-Dobzhansky-Muller (BDM) model (Bateson, 1909;Dobzhansky, 1936;Muller, 1942). However, many incompatibilities uncovered using high-throughput molecular analyses (Castillo and Barbash, 2017;Kuzmin et al, 2018;Schumer et al, 2018;Vaid and Laitinen, 2019) and quantitative trait locus (QTL) mapping (Moyle and Nakazato, 2008;Turner et al, 2014;Chae et al, 2014;Lowry et al, 2015;Wang et al, 2015), do not conform to the processes assumed by the BDM model. In particular, in both natural populations and model organisms, studies have found that reproductive barriers often exist between allopatric populations experiencing similar selection pressures and that many of the alleles underlying genetic incompatibility predate the allopatric separation of populations (Schluter, 2009;Han et al, 2017;Guerrero and Hahn, 2017;Marques et al, 2019;Jamie and Meier, 2020).…”
Section: Introductionmentioning
confidence: 99%